Coming of Age in Paolini's The Inheritance Cycle - Jelen, Tomáš (Univerzita Pardubice, 2023)
This diploma thesis analyses the first two books from The Inheritance Cycle by Christopher Paolini regarding coming of age and maturation of the main protagonist, Eragon. The first part of the work will explain and introduce to the reader the literary context of fantasy, young adult fantasy, metamorphosis, and Bildungsroman. The second part will be concerned with analysing the depiction of Eragon's development and maturation and the usage a portrayal of metamorphosis.
Dospívání v Paoliniho Odkazu dračích jezdců
Keywords: fantasy; Eragon; Paolini, Christopher; dospívání; Eldest; Roran; Safira; young adult fantasy; fantasy pro mládež; metamorfóza; Bildungsromán; fantasy; Eragon; Paolini, Christopher; Bildungsroman; coming of age; maturation; Eldest; Roran; Saphira; young adult fantasy; metamorphosis